Analisis Diskontinuitas Stabilitas Terowongan Bekas Bijih Mangan Kalilingseng Kulon Progo Berdasarkan Klasifikasi Massa Batuan - Ardya Pramesti Putri Arindry; Singgih Saptono; Barlian Dwi Nagara; S Koesnaryo; D Haryanto (Universitas Muslim Indonesia, 2023)
The Kalilingseng Tunnel is an ex-mining manganese ore mine located in Ngruno Hamlet, Karangsari Village, Pengasih District, Kulon Progo Regency, Yogyakarta Province. Now, the tunnel has been planned to be used as a geotourism where the stability of the tunnel is very important to research. Therefore, this survey was conducted to analyze the discontinuity of the tunnel to simulate in the original Young's modulus value, a decrease of 75% and 50% to the strength factor value and to analyze whether there is an influence of the seismic factor on the displacement and the strength factor. From the results of the rock mass classification investigation by Hoek and Brown’s Rock Mass Rating, it was found that the strength factor value based on Finite Element Analysis with non-linier criterion failure was more than 2 where the results were categorized as safe without any support in the tunnel so that it could be used as a geotourism location.